2013
DOI: 10.1371/journal.pone.0079087
|View full text |Cite
|
Sign up to set email alerts
|

Ultrasensitive Norovirus Detection Using DNA Aptasensor Technology

Abstract: DNA aptamers were developed against murine norovirus (MNV) using SELEX (Systematic Evolution of Ligands by EXponential enrichment). Nine rounds of SELEX led to the discovery of AG3, a promising aptamer with very high affinity for MNV as well as for lab-synthesized capsids of a common human norovirus (HuNoV) outbreak strain (GII.3). Using fluorescence anisotropy, AG3 was found to bind with MNV with affinity in the low picomolar range. The aptamer could cross-react with HuNoV though it was selected against MNV. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
92
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
3
2
2

Relationship

0
7

Authors

Journals

citations
Cited by 96 publications
(98 citation statements)
references
References 19 publications
(19 reference statements)
4
92
0
Order By: Relevance
“…Visualization and electrochemical (i.e., CV) evaluation of aptamer immobilization confirmed that MEMS electrochemical aptasensor was successfully fabricated via self-assembly of a thiolated aptamer on the gold working electrode surface following a procedure reported previously [3]. …”
Section: B Electrochemical Evaluation Of Aptamer Immobiliaztionsupporting
confidence: 62%
See 3 more Smart Citations
“…Visualization and electrochemical (i.e., CV) evaluation of aptamer immobilization confirmed that MEMS electrochemical aptasensor was successfully fabricated via self-assembly of a thiolated aptamer on the gold working electrode surface following a procedure reported previously [3]. …”
Section: B Electrochemical Evaluation Of Aptamer Immobiliaztionsupporting
confidence: 62%
“…Aptamer immobilization on the gold working electrode through the affinity between gold and thiol was carried out according to a previous study [3], with slight modification. Prior to immobilization, the fabricated MEMS sensor base was thoroughly washed with DI water and then dried with nitrogen gas (N 2 ).…”
Section: Immobilization Of Aptamers On Gold Working Electrodementioning
confidence: 99%
See 2 more Smart Citations
“…In the period considered in this review several examples have been proposed to develop electrochemical disposable sensors based on the use of DNA aptamers or DNA sequences for the detection of aptamers' targets, proteins, transcription-factors and anti-DNA antibodies [65,[90][91][92][93][94][95].…”
Section: Dna-based Electrochemical Disposable Sensorsmentioning
confidence: 99%